The Impact of Village Head Elections on Social Interaction in Baebunta Village, Baebunta District, North Luwu Regency - Pabesak, Anthon Sattu; Jaya, Apriliani Kusuma (The Future of Education Journal, 2026)
Village head elections (pilkades) represent a form of local democracy that involves active community participation. This study aims to examine the impact of village head elections on social interaction within the Baebunta Village community, from both positive and negative perspectives. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Research informants included village head candidates, village officials, community leaders, religious leaders, women leaders, youth leaders, and residents involved in the election process. The findings indicate that the village head election in Baebunta Village produces dual impacts. On the positive side, it increases community political awareness, encourages active participation in the village democratic process, and fosters cooperation between the village government and residents in development activities. However, negative impacts also emerge, including horizontal conflicts, polarization among supporters, a decline in social solidarity, and post-election group exclusivity. Data analysis reveals that community social interaction undergoes dynamic changes, shifting from political tension toward social reconciliation through collective village activities. This study concludes that village head elections function not only as political arenas but also as significant factors shaping patterns of social relationships within the community. Therefore, active involvement of the village government is required to maintain social harmony, along with reconciliation mechanisms to prevent prolonged negative impacts.